First assessment of interchange of humpback whales between Oceania and the East coast of Australia - Garrigue, Claire; Franklin, Trish; Constantine, Rochelle; Russell, Kirsty; Burns, Daniel; Poole, Michael; Paton, Dave; Hauser, Nan; Oremus, Marc; Childerhouse, Simon; Mattila, Dave; Gibbs, Nadine; et al. (J. Cetacean Res. Manage., 2020)
The interchange of individual humpback whales between the wintering grounds of Oceania (South Pacific) and the east coast of Australia were documented by individual identification photographs collected from 1999 to 2004. Interchange was assessed using regional catalogues of fluke photographs, totalling 672 individuals from Oceania (represented by New Zealand, New Caledonia, Vanuatu, Fiji, Samoa, Tonga, Niue, Cook Island, French Polynesia and American Samoa) and 1,242 individuals from Hervey Bay and Byron Bay representing the southbound and the northbound migration along the east coast of Australia (EA). Overall, there were seven documented movements between EA and Oceania. Four instances of movement of four individuals were documented between EA and the closest breeding grounds of New Caledonia. A further three movements were recorded between EA and a small catalogue (n = 13) from the New Zealand migratory corridor. In contrast, during this same period, 20 cases of interchange were documented among nine breeding grounds: French Polynesia, Cook Islands, Niue, American Samoa, Samoa, Tonga, Fiji, Vanuatu and New Caledonia. The low level of interchange between Oceania and the east coast of Australia has important implications for understanding the stock structure and abundance of humpback whales in the South Pacific.